Altered GDF15 and FGF21 Levels in Response to Strenuous Exercise: A Study in Marathon Runners - Campderrós, Laura; Sánchez-Infantes, David; Villarroya, Joan; Nescolarde, Lexa; Bayès-Genis, Antoni; Cereijo, Rubén; Roca, Emma; Villarroya, Francesc (Frontiers in Physiology, 2020)
Background. Recreational marathon runners face strong physiological challenges. Assessment of potential biomarkers for the biological responses of runners will help to discriminate individual race responsiveness and their physiological consequences. This study sought to analyze the changes in the plasma levels of GDF15 and FGF21, novel endocrine factors related to metabolic stress, in runners following the strenuous exercise of a marathon race. Methods. Blood samples were obtained from eighteen male runners (mean + SD, age: 41.7 + 5.0 years, BMI: 23.6 + 1.8) 48h before, immediately after, and 48h after a marathon race, and from age-matched sedentary individuals. The level of GDF15, FGF21, and 38 additional biochemical and hematological parameters were determined. Results. The basal levels of GDF15 and FGF21 did not differ between runners before the race and sedentary individuals. Significant increases in the mean levels of GDF15 (4.2-fold) and FGF21 (20-fold) were found in runners immediately after the race. The magnitudes of these increases differed markedly among individuals and did not correlate with each other. The GDF15 and FGF21 levels had returned to the basal level 48h post-race. The post-race value of GDF15 (but not FGF21) correlated positively with increased neutrophilia and monocytosis. Conclusion: GDF15 and FGF21 are transiently increased in runners following a marathon race. The transient increase in GDF15 (but not in FGF21) is associated with strenuous-exercise-induced alterations in the immune cell status. The induction of GDF15 and FGF21 differ in their value as potential biomarkers of runners’ responsiveness to the marathon race